Transformasi Kebijakan Desentralisasi Di Indonesia Dan Implikasinya Terhadap Stabilitas Pemerintahan Daerah Di Era Globalisasi - Lathifah, Hilma; Frinaldi, Aldri; Magriasti, Lince; Naldi, Hendra (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
The implementation of decentralization in Indonesia does not always run smoothly. Since the beginning of its implementation, various challenges have continued to emerge that hinder the effectiveness of this policy. One of the main challenges is the capacity gap between regions, where some regions are able to manage autonomy well, while others still depend on central assistance. Corruption and low accountability at the local level are also serious problems that often undermine decentralization. The aim of this research is to analyze the impact of the transformation of decentralization policies in Indonesia on the stability of regional government, as well as identify the challenges faced by regional governments in the context of globalization and their implications for political and economic stability. The research method used in this study is a literature study, which collects and analyzes various academic sources, government reports, and related documents to understand the transformation of decentralization policies and their impact on regional government in Indonesia. The research results show that the post-1998 Reformation decentralization policy transformation had a significant impact on regional governance, but also gave rise to complex challenges, such as central-regional conflict and budget inequality, which affected political and economic stability. In the context of globalization, this challenge emphasizes the importance of collaboration and strengthening human resource capacity, as well as the need for synergy between central, regional governments and community participation to achieve better stability.